Relationship between degree of polymeric ionisation and hydrolytic degradation of Eudragit® E polymers under extreme acid conditions (2019)
ABSTRACT: The commercial copolymers Eudragit® E 100 and Eudragit® PO are widely used materials in the pharmaceutical field as coating systems. Such materials derived from amino-methacrylate groups under acidulated conditions may acquire an ionisable fraction or undergo hydrolytic degradation of the polymeric structure. This work focused on establishing the chemical, physical, and surface changes of two reprocessed polymeric materials, here named as EuCl-E-100 and EuCl-E-PO, which were obtained from the commercial Eudragit® E 100 and Eudragit® E PO, respectively. The commercial materials were exposed to extreme acid conditions, where the polymers were solubilised and subsequently dried by the refractance window method. The materials obtained were chemically characterised by potentiometric titration, nuclear magnetic resonance spectroscopy (1H NMR and 13C NMR) in one and two dimensions (COSY, HSQC, and HMBC), infrared spectroscopy, X-ray diffraction, and differential scanning calorimetry. Changes in the physical properties of the materials were evaluated through studies of flowability, compactability, and their ability to gain and lose humidity. Surface thermodynamic studies were carried out through contact angle measurements using the sessile drop method. The results showed that the processed polymeric materials acquired a substantial degree of ionisation without undergoing hydrolysis of the esterified groups. Furthermore, such changes improved the flow characteristics of the material and the solubility in aqueous media at pH > 5, while also maintaining the hydrophobicity degree of the polymeric surface.